2004
DOI: 10.1139/y04-086
|View full text |Cite
|
Sign up to set email alerts
|

Differential participation of protein kinase C and Rho kinase in α1-adrenoceptor mediated contraction in rat arteries

Abstract: The major functional alpha1-adrenoceptor in the rat aorta is of the alpha1Dsubtype and that in the caudal artery is of the alpha1A subtype. In the present study, the participation of protein kinase C (PKC) and Rho kinase (RhoK) in contractile responses to stimulation of the alpha1-adrenoceptors in these two arteries was investigated. Both the PKC inhibitor Ro-318220 and the RhoK inhibitor Y-27632 significantly blocked contractile responses of the aorta to phenylephrine (PE) and the selective alpha1A-adrenocept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
4
13
1
Order By: Relevance
“…Additionally, we showed that reductions in NE responses in the presence of chelerythrine at 2.5 M were significantly greater than corresponding reductions with KCl responses. These findings are in agreement with a demonstrated link of PKC to activation of the adrenergic pathway in VSM, while inhibition of K ϩ -depolarized VSM would imply a more general nonspecific effect on the vessels (35). We therefore conclude that the absence of myogenic reactivity in the presence of chelerythrine at 2.5 M was not explained by the complete suppression of VSM contractility, but rather is due, in part, to the effects of PKC inhibition (53).…”
Section: R475supporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, we showed that reductions in NE responses in the presence of chelerythrine at 2.5 M were significantly greater than corresponding reductions with KCl responses. These findings are in agreement with a demonstrated link of PKC to activation of the adrenergic pathway in VSM, while inhibition of K ϩ -depolarized VSM would imply a more general nonspecific effect on the vessels (35). We therefore conclude that the absence of myogenic reactivity in the presence of chelerythrine at 2.5 M was not explained by the complete suppression of VSM contractility, but rather is due, in part, to the effects of PKC inhibition (53).…”
Section: R475supporting
confidence: 89%
“…This highlights the important role played by calcium sensitization in myogenic reactivity of veins, which enables vessels to maintain a range of pressure-induced vascular tone without large changes in intracellular calcium (53). Although most studies suggest that PKC and RhoA/Rho kinase pathways are activated independently to cause VSM contraction, cross talk between them has been suggested (35). It is therefore conceivable that inhibition of each of these pathways, i.e., PKC or Rho kinase could produce substantial reductions in myogenic reactivity.…”
Section: R475mentioning
confidence: 99%
“…In rat tail artery, a1-adrenoceptormediated calcium sensitisation is due mainly to the activation, via the small GTP binding protein RhoA, of Rho kinase [123], which phosphorylates and so inhibits myosin light-chain phosphatase (see [124]) (see Fig. 2).…”
Section: Receptor Dimers and Oligomersmentioning
confidence: 99%
“…Recently, this issue has been addressed in a series of experiments on intact blood vessels. This study reported a nonparallelism between ␣ 1 -AR-mediated IP formation and smooth muscle contraction in the rat aorta (12), which is possibly a result of sensitization mediated by intracellular enzymes, such as Rho kinase and PKC (31,48). Moreover, there is convincing evidence for activation of other signaling pathways by ␣ 1 -AR.…”
Section: Discussionmentioning
confidence: 59%